A retrospective study of perforation peritonitis in a tertiary care hospital in Uttar Pradesh, India - Mukherjee, Sujoy; Raza, Mohd. Arshad; Jindal, Rishi; Ratnakar, Ratnakar (International Surgery Journal, 2016)
Background: Perforation peritonitis is a common surgical emergency encountered by surgeon’s world over. The spectrum of this disease including its etiology differs in various countries. The present study was carried out to study the various modes of presentation, clinical features morbidity and mortality of perforation peritonitis in a tertiary care hospital in Uttar Pradesh, India. Methods: This study was conducted on 221 consecutive patients of perforation peritonitis who presented in a period of 2 years (March 2014 to February 2016) in department of surgery, Rohilkhand medical college and hospital, Bareilly, Uttar Pradseh, India. These patients were assessed with respect to clinical presentations, causes, site of perforation, surgical management, postoperative complications and mortality if any. Following resuscitative measures, all patients underwent emergency exploratory laparotomy, where the cause of perforation was explored and controlled. Results: A total of 221 cases of perforation peritonitis were included in the study with mean age of 39.8 years (range = 10 - 70 years). Majority of patients were male with female ratio of 4.02:1. 62% came with complaints of distension and 42% gave positive history of chronic NSAID use. Most common complications were wound infection, septicemia and dyselectrolylemia (49, 40 and 46% respectively). The overall mortality was 12.2%. Conclusions: In the present study, most common site of perforation was the duodenum, the cause being acid peptic disease as a consequence of NSAIDs use. Early recognition, prompt intervention might lead to better outcomes and curtail mortality and morbidity associated with this disease. Highest percentage of perforation was noted in upper part of gastrointestinal tract.